Electrochemical studies of 2-amino-1, 9-dihydro-9-((2- hydroxyethoxy) methyl)-6h-purin-6-one as green corrosion inhibitor for mild steel in 1.0 m hydrochloric acid solution - Verma C.; Quraishi M.A.; Ebenso E.E. (My University, 2025)
The influence of Acyclovir (2-amin-1,9-dihydro-9-((2-hydroxyethoxy)methyl)-6H-purin-6-one) on the corrosion rate of Mild Steel in 1.0 M HCl was investigated by gravimetric and electrochemical methods. It was found that the Acyclovir acts as an efficient corrosion inhibitor for mild steel in 1.0 M HCl. The inhibition efficiency increases with increasing the inhibitor concentration. The maximum efficiency was found to be 92% at 500ppm concentration. The adsorption of Acyclovir drug on the mild Steel surface follows the Langmuir adsorption isotherm. The electrochemical results indicated that the investigated compound acts as mixed-type inhibitor. Some thermodynamic parameters were also determined to investigate the mechanism of corrosion inhibition. © 2013 by ESG.